Devices for donor lung preservation. (2nd December 2022) - Bisbee, Cora R; Sherard, Curry; Kwon, Jennie; Hashmi, Zubair A; Gibney, Barry C.; Rajab, Taufiek
ABSTRACT: Introduction: Lung transplantation is the gold standard for the treatment of end stage lung disease but is limited by donor availability. Recently, the donor pool has seen significant expansion with liberalization of donor criteria. However, extended criteria donors can require additional time to prepare for implantation, necessitating additional preservation time of donor lungs. Areas covered: We present a review of current lung transplant storage strategies including new methodologies and technological advancements. The current standard, static cold storage, is a simple and cost-effective method of preserving grafts, but offers little flexibility with limited ability to mitigate ischemic-reperfusion injury, inflammation, and hypothermic tissue damage. Novel ex vivo lung perfusion (EVLP) devices, TransMedics OCS and XVIVO perfusion systems, extend preservation time by perfusing, and ventilating donor lungs while simultaneously allowing for evaluation of lung viability. Perfusate, preservation solutions, additives, temperature regulation, and assessment of organ damage are all critical components when evaluating the success and outcomes of these devices. Expert Opinion: EVLP devices are more costly and often require additional resources and personnel support compared to static cold storage, but may provide the opportunity to extend preservation time, perform functional assessment, mitigate ischemic injury, and optimize extended criteria donors.